Acute Lung Injury and the NLRP3 Inflammasome - Gu W; Zeng Q; Wang X; Jasem H; Ma L (Dove Medical Press, 2024)
Wanjun Gu, Qi Zeng, Xin Wang, Huthaifa Jasem, Ling Ma Department of Anesthesiology, Shengjing Hospital of China Medical University, Shenyang, People's Republic of ChinaCorrespondence: Ling Ma, No. 36 Sanhao Street, Heping District, Shenyang, 110004, People's Republic of China, Tel +86-18940256927, Email mal@cmu.edu.cnAbstract: Acute lung injury (ALI) manifests through harm to the capillary endothelium and alveolar epithelial cells, arising from a multitude of factors, leading to scattered interstitial alterations, pulmonary edema, and subsequent acute hypoxic respiratory insufficiency. Acute lung injury (ALI), along with its more serious counterpart, acute respiratory distress syndrome (ARDS), carry a fatality rate that hovers around 30- 40%. Its principal pathological characteristic lies in the unchecked inflammatory reaction. Currently, the main strategies for treating ALI are alleviation of inflammation and prevention of respiratory failure. Concerning the etiology of ALI, NLRP3 Inflammasome is essential to the body's innate immune response. The composition of this inflammasome complex includes NLRP3, the pyroptosis mediator ASC, and pro-caspase-1. Recent research has reported that the inflammatory response centered on NLRP3 inflammasomes plays a key part in inflammation in ALI, and may hence be a prospective candidate for therapeutic intervention. In the review, we present an overview of the ailment characteristics of acute lung injury along with the constitution and operation of the NLRP3 inflammasome within this framework. We also explore therapeutic strategies targeting the NLRP3 inflammasome to combat acute lung injury.Keywords: acute lung injury, NLRP3 inflammasome, caspase-1, IL-1β, IL-18